Identification of some Intestinal Helminthes In Barbu grypus, Liza abu and study of histopathological changes Result from infection - M.Al - Mayali, Hadi; M.Y.Al-mahi, Asifa (Al-Qadisiyah Journal of Pure Science, 2018)
The present study has been conducted in four parts of Diwaniya (Diwaniya center, Shamiya,Hamza and Afaq). A sample of 945 fish of Barbus grypus and Liza abu has been examined . It was found that 205 of the Barbus grypus fish and 344 of the Liza abu were infected with parasitic intestinal worms. Some parasitic intestinal worms have been detected such as the Neoechinorynchus iraqensis in both fish types. The female paulisentus Bothriocephalus acheilognathi were found in the Barbus grypus and the larva of Contracaecum sp was seen in the Liza abu type In Diwaniya river had high infection of both fish types was 61.31% . The Barbus grypus fish were recorded with 70.11% while the Liza abu fish infection was 57.21%. The Liza abu infection in the four parts of Diwaniya as 56.30% In September the infection percentage was higher by 63.21% in the two kinds of fish . while in February, December the infection rate was as low as 50%. It was also found that length categories of ( 26-24.1)cm of Barbus grypus had high percentage of 67.16% , infection with intestinal worms in thelengthcategory(>-30.1) was 22.22%. As for the Lizaabuithada high perentage of infection in length category (12-10.1) cm , the percentage was 67.53%.The present study has discovered many pathological changes (visable and microscopic)caused by the intestinal worms , Among the visable changes was embolism and bleeding of the walls of the infected intestinal microscopic changes included an increase in the phlogistic and phagocytic cell and ruining of the internal tissue lining the intestines and atrophy villi.